Learning the Smart Way: Lessons Learned by the Reaching Agents of Change Project - Mbabu, A.N.; Munyua, H.M.; Mulongo, G.; David, S.; Brendin, M. (International Potato Center, 2015)
The Reaching Agents of Change (RAC) project was a pilot that advocated for increased investment in orange-fleshed sweetpotato to combat vitamin A deficiency among young children and women of reproductive age. It was implemented by the International Potato Center and Helen Keller International primarily in Nigeria, Mozambique, Tanzania and to a lesser extent in Ghana and Burkina Faso between 2011 and 2014. The project had multiple deliverables in advocacy for raising of new investment, policy change and strengthening of institutional and individual capacities in the project countries. RAC incorporated a systematic and comprehensive results-based monitoring and evaluation system and continuously documented the implementation process over the project period. This booklet shares the learning process that RAC adopted and highlights some useful and replicable lessons learned.